Ragam Penafsiran Netizen tentang Pemimpin Non-Muslim: Telaah atas Penafsiran Surat al-Maidah Ayat 51 - Helmy Zakariya (IAIN Surakarta, 2017)
Internet media has an important role in the process of interpretation today. Before the arrival of this new medium, knowledge of religion is accessed through the literature of the books of Tafseer, fiqh, and other books. Nowadays people are getting easier to access anything with internet media including religious material. This article specifically discusses how netizens interpret al-Maidah: 51 which became a trending topic some time ago related to the national issue of non-Muslim leaders in the majority Muslim community. This discussion focuses on two questions. First, How does the role of netizens interpret al-Maidah: 51. Second, How about Netizen's understanding of choosing non-Muslim leaders? In this article, the author collects a variety of writings from the netizens who write al-Maidah's commentary in the internet media. The results showed that netizens used a variety of methods. Some netizens discussed it with the usual steps in the science of exegesis. Some others tend to take only a few steps to quote the opinions of the former Mufassir. In this case, the more complete the approach used the more effective the interpretation result will be. From this explanation can also be underlined that the interpretation circulating on the internet enough to give a new color for the development of contemporary interpretation and become a reference for each reader.